2024
DOI: 10.26434/chemrxiv-2024-rk4qx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning-driven models for predicting CO2 Uptake in Metal-Organic Frameworks (MOFs)

Sofiene Achour,
Zied Hosni

Abstract: This study advances the discourse on the application of machine learning (ML) algorithms for the predictive analysis of CO2 uptake in Metal-Organic Frameworks (MOFs), with a nuanced focus on the CATBoost model's capability to navigate the complexities inherent in MOFs' heterogeneous landscape. Building upon and extending the comparative analysis, our investigation underscores the CATBoost model's remarkable predictive prowess, characterized by a significant reduction in root mean square error (RMSE) and an enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…CO 2 is the most significant component of GHGs emissions and the primary cause of global warming. According to a report, atmospheric CO 2 concentrations have increased from approximately 310 ppm to over 380 ppm in the last five decades. In 2024, Achour utilized ML algorithms to predict and analyze the absorption of CO 2 by MOFs, with a focused investigation on applying the CATBoost model . The study found that the CATBoost model demonstrated significant predictive capability, accurately and reliably forecasting CO 2 adsorption.…”
Section: Combine Mofs With ML For Ghg Emissionmentioning
confidence: 99%
“…CO 2 is the most significant component of GHGs emissions and the primary cause of global warming. According to a report, atmospheric CO 2 concentrations have increased from approximately 310 ppm to over 380 ppm in the last five decades. In 2024, Achour utilized ML algorithms to predict and analyze the absorption of CO 2 by MOFs, with a focused investigation on applying the CATBoost model . The study found that the CATBoost model demonstrated significant predictive capability, accurately and reliably forecasting CO 2 adsorption.…”
Section: Combine Mofs With ML For Ghg Emissionmentioning
confidence: 99%